Library of electrocatalytic sites in nano-structured domains: Electrocatalysis of hydrogen peroxide - Pandey P.C.; Singh B. (My University, 2025)
Electrochemical detection of hydrogen peroxide at eight types of ormosil-modified electrodes, referred as hexacyanoferrate-system; Prussian blue systems (PB-1, PB-2, and PB-3), palladium (Pd-) system, graphite (Gr-) system, gold nanoparticle (AuNPs) system and palladium-gold nanoparticle (Pd-AuNPs) system were studied. The results on electrochemical detection suggested that hydrogen peroxide does not undergo homogeneous electrochemical mediation; however, the presence of redox mediator within nano-structured domains facilitates the electro-analysis of the same via redox electrocatalysis. Four approaches causing manipulation in nano-structured domains are described: (a) increase in the molecular size of the components generating nano-structured domains; (b) modulation via chemical reactivity; (c) modulation by non-reactive moieties and known nanoparticles; and (d) modulation by mixed approaches (a-c), all leading to decrease in a nano-structured domains. The results demonstrated that an increase in the size of nano-structured domains or decrease in micro-porous geometry increases the efficiency of electrocatalysis. The basic reaction protocol adopted in generating nano-structured domains, followed by manipulation protocols, supported the introduction of a library for creating electrocatalytic sites with varying electrocatalytic efficiency within the same basic nano-structured platform. © 2008 Elsevier B.V. All rights reserved.